Satellite Estimation and Ground Based Measurements of Solar UV Index in Kathmandu - Sharma, Niranjan Prasad (Journal of the Institute of Engineering, 2014)
The study is based on the satellite estimation and ground measurements of solar UV index in Kathmandu for the year 2009. Kathmandu (27.720N, 85.320E) is located at an elevation of 1350m from the sea level. The ground based measurement and satellite estimation was performed by NILU-UV irradiance meter and EOS Aura OMI spacecraft. The NILU-UV irradiance meter measures UV radiation in different spectral range. The Ozone Monitoring Instrument (OMI) is a spectrometer designed to monitor solar radiation in spectral range of (270-500) nm. This study shows that satellite overestimates the ground based (GB) UV Index (UVI) before monsoon by 103.6 % whereas during the monsoon period overestimation comes down to 70.8 %. The correlation coefficient (r) between ozone column from satellite and ground based measurement before monsoon and after monsoon is also studied. It is observed that the correlation between satellite estimated ozone column and ground based ozone column before and after monsoon is 0.83. The study showed that the estimation of OMI before monsoon is high than after monsoon. DOI: http://dx.doi.org/10.3126/jie.v9i1.10664 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 18–26